The Role of Nutritional Status, Dietary Pattern and Free Radical in the Insulin Resistance Development - Meirna Dewita Sari; Bambang Wirjatmadi; Merryana Adriani (Humanistic Network for Science and Technology (HNST), 2017)
Insulin resistance is an early sign of diabetes type 2 that occurs in situations where target organ sensitivity decreases against insulin. Excess free radicals can be mutually insulin resistance. The purpose of this study was to determine how the effects of insulin can be a determining factor. This study used case control design conducted on 22 outpatients at Clinic University of Muhammadiyah Surabaya during June until July 2017. Data were collected using questionnaires, nutritional status, fasting blood glucose, fasting insulin, and MDA levels. Insulin resistance status using normal HOMA IR method of <2.77. Logistic Regression was used to determine the effect of free radical on the occurrence of insulin resistance. The results showed free radical against insulin resistance at =0.05 with p=0.018. That result means boosting MDA levels also increases the risk of insulin resistance. In addition, the consumption of dietary sources of fat and excessive use of food additives, low fruit intake, BMI values are also factors affecting insulin resistance with p=0.027; p=0.036; and p=0.027. Given the elevated levels of MDA-free radicals can increase the risk of insulin resistance. Applying a healthy lifestyle by consuming fiber-rich foods can prevent the formation of excessive free radicals. Keywords: Insulin resistance, Free radical, HOMA IR